An exploratory study of crisis leadership demonstrated by Mayor Rodrigo R. Duterte during the Davao International Airport and Sasa Wharf bombings in 2003 - Demerin, Margilei C.
Although crises are prevalent, there a lack of empirical research gap. This qualitative research basically explores Mayor Duterte's leadership strategies from the perspectives of Schoenberg's (2005) values and characteristics of a successful crisis leader, Braden, et. al.'s (2005) seven essential crisis leadership strategies, and Sellnow's (2001) standpoint on communication. The personal interview with the mayor was the primary source of data for this study supplemented with news reports from Sun Star News Online. I developed a crisis leadership model was develop from a Duterte-type of leadership evident during the bombing incidents in Davao City. Mayor Duterte as a crises leader is at the center of the entire crisis management process. He demonstrated all of the seven essential crisis leadership strategies and embodied the communication process. This study revealed that the Davao bombings as crisis situations were in fact an opportunity for a leader and a crisis management team to work closely of despite inadequate preparation. In the case of the Davao bombings for instance, it is the leader and the personal attributes he exhibited that made the difference. A crisis leader should provide an order in the system of the entire crisis management. If a leader can not stand on his own feet, then it would only cripple some parts of the management system. Therefore, if leadership fails the crisis management efforts would collapse. Crisis leaders should take serious consideration of studying and adopting the leadership model developed by this researcher in order to examine their leadership skills and evaluate their set of values to become more effective crisis management leaders.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication